Seychelles : 2022 Article IV Consultation, Second Review Under the Extended Fund Facility Arrangement, and Request for Modification of Performance Criteria and Indicative Targets-Press Release; Staff Report; and Statement by the Executive Director for Seychelles. (IMF Staff Country Reports; Country Report, 2022)
Seychelles' economic recovery in 2021 vastly outperformed projections, fueled by a faster-than-expected rebound of the tourism sector. The recovery is expected to continue in 2022 with projected real GDP growth of 7.1 percent as the tourism sector shows resilience to COVID-19 waves and geopolitical tensions. The recovery has been accompanied by a significant fiscal overperformance.